Hubungan Pengetahuan dan Pola Asuh Orang Tua tentang Gizi Seimbang dalam Pencegahan Gizi Kurang pada Balita - Sihite, Helprida; Sinaga, Mega Silvia; Mayes Felda Simamora (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to examine the relationship between parental knowledge and parenting styles regarding balanced nutrition in preventing malnutrition among toddlers in Pasingguran 1 Village, Pollung Subdistrict, Humbang Hasundutan Regency. This research utilized a descriptive-analytic method with a cross-sectional approach, involving 31 respondents. The results showed a significant relationship between parental knowledge and the prevention of malnutrition (p-value < 0.05) as well as between parenting styles and the prevention of malnutrition (p-value < 0.05). The study concludes that good knowledge and supportive parenting styles significantly influence efforts to prevent malnutrition among toddlers. Therefore, improving parental knowledge and appropriate parenting practices should be a primary focus in health interventions to reduce the prevalence of malnutrition in the region.